2022
DOI: 10.1097/prs.0000000000010088
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Nerve Gap Repair: Comparative Effectiveness of Allografts, Autografts, and Conduits

Abstract: Background: Ideal nerve repair involves tensionless direct repair, which may not be possible after resection. Bridging materials include nerve autograft, allograft, or conduit. This study aimed to perform a systematic literature review and meta-analysis to compare the meaningful recovery (MR) rates and postoperative complications following autograft, allograft, and conduit repairs in nerve gaps greater than 5 mm and less than 70 mm. A secondary aim was to perform a comparison of procedure costs. Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…16,27 These preclinical results may not be apparent clinically, as a meta-analysis published recently concluded that there were no significant meaningful recovery differences between autograft and allograft nerve reconstructions across short and long nerve gaps. 9,10 Although our current study did not investigate functional outcomes, future studies should consider the influence of fascicular area on functional outcomes. Although it is currently unknown if the differences in the regenerative area noted in this study lead to meaningful differences in clinical outcomes, previous basic scientific studies indicate that the available neural tissue (fascicular area) in the intercalary graft segment may influence potential nerve regeneration and distal reanimation.…”
Section: Discussionmentioning
confidence: 91%
“…16,27 These preclinical results may not be apparent clinically, as a meta-analysis published recently concluded that there were no significant meaningful recovery differences between autograft and allograft nerve reconstructions across short and long nerve gaps. 9,10 Although our current study did not investigate functional outcomes, future studies should consider the influence of fascicular area on functional outcomes. Although it is currently unknown if the differences in the regenerative area noted in this study lead to meaningful differences in clinical outcomes, previous basic scientific studies indicate that the available neural tissue (fascicular area) in the intercalary graft segment may influence potential nerve regeneration and distal reanimation.…”
Section: Discussionmentioning
confidence: 91%
“…However, it is important to note that compared with the current study, the Lans study was conducted with Medicare fee-for-service hospital claims, and, in addition, multivariable analysis was not conducted to explore adjusted cost differences between the nerve repair types. 19 Not surprisingly, among inpatients and outpatients, mean implantable cost was significantly higher for allograft versus autograft nerve repair procedures but this was offset by savings in OR and R&B costs among allograft cases. A higher implantable cost was also observed among inpatient versus outpatient allograft nerve repair cases.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is important to note that compared with the current study, the Lans study was conducted with Medicare fee-for-service hospital claims, and, in addition, multivariable analysis was not conducted to explore adjusted cost differences between the nerve repair types. 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations